2021
DOI: 10.3390/antibiotics10070847
|View full text |Cite
|
Sign up to set email alerts
|

The Phagosome–Lysosome Fusion Is the Target of a Purified Quillaja saponin Extract (PQSE) in Reducing Infection of Fish Macrophages by the Bacterial Pathogen Piscirickettsia salmonis

Abstract: Piscirickettsia salmonis, the etiological agent of Piscirickettsiosis, is a Gram-negative and facultative intracellular pathogen that has affected the Chilean salmon industry since 1989. The bacterium is highly aggressive and can survive and replicate within fish macrophages using the Dot/Icm secretion system to evade the host’s immune response and spread systemically. To date, no efficient control measures have been developed for this disease; therefore, the producers use large amounts of antibiotics to contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 105 publications
(158 reference statements)
0
4
0
Order By: Relevance
“…According to the transcriptomic data, the phagosome and lysosome pathways were significantly enriched in the vaccinated fish hindgut ( p ≤ .05). Notably, the formation of a phagolysosome by the fusion of phagosome and lysosome demonstrated various bactericidal properties (Cortés et al., 2021). Lysosomes, a membrane‐bound cell organelle that contains digesting enzymes such as lysozyme, are essential for fish's non‐specific immunological response (Abdollahi et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…According to the transcriptomic data, the phagosome and lysosome pathways were significantly enriched in the vaccinated fish hindgut ( p ≤ .05). Notably, the formation of a phagolysosome by the fusion of phagosome and lysosome demonstrated various bactericidal properties (Cortés et al., 2021). Lysosomes, a membrane‐bound cell organelle that contains digesting enzymes such as lysozyme, are essential for fish's non‐specific immunological response (Abdollahi et al., 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Although quillaja extracts have been used extensively as emulsifiers for foods and beverages, foaming agents, nematicides in agriculture and in many other applications [ 18 , 19 ], it is well known that some quillaja saponins are able to block viral and bacterial association with cells, as well as modulate intracellular processes. These biological effects lead to the induction of an innate and adaptive immune response, including cellular and humoral types [ 20 ]. High-grade quillaja extracts containing ≥90% w / w saponins (dry basis) can be employed as immunostimulant agents (vaccine adjuvants) in veterinary and human vaccine formulations [ 20 , 21 ], where they effectively modify the activities of antigen-presenting cells (macrophages and dendritic cells).…”
Section: Introductionmentioning
confidence: 99%
“…These biological effects lead to the induction of an innate and adaptive immune response, including cellular and humoral types [ 20 ]. High-grade quillaja extracts containing ≥90% w / w saponins (dry basis) can be employed as immunostimulant agents (vaccine adjuvants) in veterinary and human vaccine formulations [ 20 , 21 ], where they effectively modify the activities of antigen-presenting cells (macrophages and dendritic cells). It has been demonstrated that quillaja saponins, alone or incorporated into immune-stimulating complexes (ISCOMs), modulate immunity responses in different ways: by increasing antigen uptake in antigen-presenting cells (APC), by stimulating Th1 and Th2 immune responses to different antigens, and by inducing cytotoxic T lymphocytes (CTL) [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation